PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS VIII PADA MATA PELAJARAN IPS DI SMP NEGERI 12 PADANG - Ariyadi; Sri Rahayu; Harisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model on students’ critical thinking skills in social studies learning at SMP Negeri 12 Padang. The background of the study is based on the low level of students’ critical thinking ability due to the dominance of conventional teaching methods. This research employed a quasi-experimental method with a pretest-posttest control group design. The research subjects were class VIII.5 as the experimental group and class VIII.4 as the control group. The instrument used was an essay test that had been validated by subject matter experts and analyzed using IBM SPSS Statistics version 29. The N-Gain analysis indicated that the experimental class showed a higher average improvement compared to the control class, with gains of 27.55% in the experimental class and 9.81% in the control class, although both were still categorized as low. The Mann-Whitney U test was used due to the non-normal distribution of data, and the results showed a significance value of 0.017 < 0.05, indicating a significant difference in posttest results between the two groups. These findings suggest that the PBL model is more effective than conventional teaching methods in enhancing students' critical thinking skills in social studies. Therefore, the implementation of PBL is recommended as an alternative instructional strategy to strengthen students' analytical and problem-solving abilities at the junior high school level.